Posisi Head Up Dapat Meningkatkan Saturasi Oksigen Pada Pasien Stroke : Literature Review - Sholekhah, Elysa Mar’atus; Suyanto, Suyanto (Madago Nursing Journal, 2023)
Stroke is one of the most common diseases in society. One of the nursing management of critical stroke patients is head-up intervention. Objective: to identify whether the head-up position affects the increase in oxygen levels in stroke patients. Research Methods: This type of research is a Literature Review study. The research was conducted by entering the keywords Head Up Position, Oxygen Saturation, and Stroke in the database. Then articles were selected based on inclusion and exclusion criteria. The articles used are articles published in the last 5 years. Results: A number of eight articles said that the head-up position can increase oxygen saturation, whereas two articles said that head up had no effect on increasing oxygen saturation levels. Conclusion: Based on search results and article analysis, it was found that the concept of the head-up position can increase oxygen saturation in stroke patients and cannot be maintained. Suggestion: the concept of the head-up position can increase blood oxygen levels in stroke patients not to be maintained until there are further studies with stronger results